Across the campuses and around the globe: Reaching online learners through high-level embedded librarianship. Issue 1 (3rd April 2018) - Lysiak, Lori; Mross, Emily; Raish, Victoria
Abstract: In response to strategic and administrative goals, a large R1 public university with 24 campuses developed a programmatic embedded librarian pilot in 2016. This pilot provided high-level embedded librarianship to a growing online education program with learners located domestically and abroad. Embedded teams included librarians at regional campuses, instructional designers, and course faculty. Together the teams created new support systems and resources for online learners. This case study offers reflections and considerations for a team-based approach to high-level embedded librarianship online. Ultimately, the authors determined that successful programmatic embedded librarianship must be strategic and intentional with carefully cultivated, team-designed courses.